2003
DOI: 10.1002/rcm.1156
|View full text |Cite
|
Sign up to set email alerts
|

Identification of plant sterols in hexaploid and tetraploid wheats using gas chromatography with mass spectrometry

Abstract: Free sterols from hexaploid and tetraploid free-threshing wheats (Triticum aestivum L. and T. durum Desf.) and from their respective hulled wheats (T. spelta L. and T. dicoccon Schrank) were analysed by gas chromatography with mass spectrometry. The qualitative analysis of sterols showed a similar pattern either between hexaploid (T. aestivum, T. spelta) and tetraploid (T. durum, T. dicoccon) wheats or between free-threshing (T. aestivum, T. durum) and hulled (T. spelta, T. dicoccon) wheats. However, quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 27 publications
7
42
1
Order By: Relevance
“…The peak marked with an asterisk corresponds to hexacosanoic acid, methyl ester (see text) mass of the empirical formula of the side chain as well as the series to which compounds belong in the steroid series (Cherif et al 2009). In addition, it is noticed that when the side chain is saturated, the molecular ion is usually more abundant (Pelillo et al 2003). The saturated side chain observed here for both mitsumata and gampi reference papers corresponds to C 10 H 21 : this observation permitted to associate the detected phytosterol compounds to stigmastane-based structures.…”
Section: Identification Of Plant Markers On Reference East Asian Paperssupporting
confidence: 62%
See 1 more Smart Citation
“…The peak marked with an asterisk corresponds to hexacosanoic acid, methyl ester (see text) mass of the empirical formula of the side chain as well as the series to which compounds belong in the steroid series (Cherif et al 2009). In addition, it is noticed that when the side chain is saturated, the molecular ion is usually more abundant (Pelillo et al 2003). The saturated side chain observed here for both mitsumata and gampi reference papers corresponds to C 10 H 21 : this observation permitted to associate the detected phytosterol compounds to stigmastane-based structures.…”
Section: Identification Of Plant Markers On Reference East Asian Paperssupporting
confidence: 62%
“…For those compounds, loss of methyl at C13, successive fragmentations of ring D, and fragmentation of ring B associated to H transfer permit to elucidate the structure of their skeleton and the position of unsaturation (Table 1 and Table S3). Generally, rupture of the ring D or retro Diels Alder reaction on ring B give rise to highly diagnostic ions (Pelillo et al 2003). In particular, position of the exo ketone at C7 is defined through the fragmentation of ring C leading to the ions at m/z 159 and m/z 174 for compound 21 (Table S3).…”
Section: Identification Of Plant Markers On Reference East Asian Papersmentioning
confidence: 99%
“…Phytosterol, consumed with the diet, can influence cholesterol metabolism and the main health‐promoting effect is lowering of serum cholesterol . It has been demonstrated that although tetraploid and hexaploid wheat sterol profiles were qualitatively the same, they differed significantly on the basis of the relative amounts of specific compounds …”
Section: Introductionmentioning
confidence: 99%
“…In cereals, phytosterol determination of saponified and/or acid-hydrolyzed samples is usually performed by gas chromatography/mass spectrometry (GC/MS) after derivatization (2, [4][5][6][7][8][9]. Alkaline and acid hydrolyses release the sterol moiety of HSE/SE and SG/ASG, respectively.…”
Section: Introductionmentioning
confidence: 99%